A SIX-MONTH ORGANISATION - Jewison, Richard (My University, 2011)
Service delivery by public sector institutions is arguably one of the greatest challenges facing South Africa. There have been many processes embarked upon to bring about improvements. Rarely are the processes written up and the outcomes assessed so that lessons can be learned for both the institution concerned and those engaged generally in transformation in the public sector. This study attempts to do that, in that it documents an entire process and examines the state of an organisation, including the emerging culture, six months after its establishment. It is a case study in organisational change in a public entity. The Mpumalanga Economic Growth Agency (MEGA) was formed as a result of a merger of two existing agencies. The merger process started in September 2005 with an OD intervention in support of a Task Team established by the provincial government to bring about the merger. The merger took place on 1 April 2006, and six months was spent establishing the new organisational structure, placing staff in the new structure, developing policies, systems, processes and so on. Six months after the establishment of MEGA this study assesses the effectiveness and efficiency of MEGA, looking at whether it is doing what it set out to do, and how well it is doing it. It then goes on to examine the emerging culture of the agency. The study finds that significant progress has been made towards establishing an effective and efficient agency but that a great deal of work still needs to be done. In relation to culture, much remains of the old way of doing things and there are only small signs of a new MEGA culture emerging. Some suggestions on how to develop a discussion on culture are offered. ii The research supports the generally accepted view that transformation processes take time, that culture is very resilient, and that a holistic organisation wide approach is required rather than piecemeal interventions. A concluding observation is that the process followed in bringing about change is important. The greater the involvement of managers and staff, the greater the buy in and energy produced in implementing the agreed changes
MM - P&DM
Keywords: Service delivery; Mpumalanga Development Agency